Análise da percepção ambiental e destinação dos resíduos eletroeletrônicos no município de Itaú-RN - Gomes, Lara Poliana Melo (Universidade Federal Rural do Semi-Árido, 2018)
The generation of the waste electrical and electronic equipment (WEEE) has been growing more and more, due to the technological innovations, to the shortening of the useful life of waste electrical and electronic equipment and, above all, due to the increase of consumption in society. Consequently, such waste causes environmental problems and affects human health when is discarded incorrectly. Given these questions, the present work aimed to analyze the environmental perception and the destinations of this type of waste equipment in Itaú/RN. To this purpose, bibliographic and field research were carried out, alongside with the application of questionnaires and visits in the places of waste disposal, as well as a qualitative and quantitative analysis of the results obtained. It was verified that there is predominance in the unfamiliarity with the WEEE. It is possible to notice that the majority of respondents do not know what the proper destination to this type of waste is and that they leave the waste electrical and electronic equipment to be collected by the local collect service. The data obtained proves the deficit in the offer of collection points in the municipality and the absence of a management plan to the solid waste, specially the WEEE. In this vein, it is concluded that the dissemination of information on the theme and the development of sustainable actions, as well as the environmental perception, can reduce the inappropriate disposal of the WEEE and contribute to the construction of environmentally conscious ideas and actions.
Analysis of environmental perception and disposal of electronic waste in the city of Itaú-RN
Monografia
Keywords: Percepção ambiental; Destinação inadequada; Resíduos eletroeletrônicos; Impactos ambientais; Environmental perception; Inappropriate destination; Waste electrical and electronic equipment (WEEE); Environmental impacts; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA